Community Systems Strengthening for HIV Care: Experiences From Uganda - Mburu, Gitau; Oxenham, Danielle; Hodgson, Ian; Nakiyemba, Alice; Seeley, Janet; Bermejo, Alvaro (Journal of Social Work in End-Of-Life & Palliative Care, 2013)
The growing HIV burden on families and health systems is exerting a shift toward community caregivers, and is increasing the demand for functional community systems. In Uganda, where the number of people with HIV is increasing against a background of weak health systems, the role of community systems is poorly understood. We investigated the role of community systems in palliative care and the system elements required for an effective community response in Uganda. Qualitative interviews and focus group discussions were conducted among providers and recipients of palliative care, their family members, and governmental and community stakeholders in Mbale and Jinja, Uganda. Results showed that
Keywords: palliative care; HIV; community systems; Uganda